Realism, Representation, and Ideology: A Fiskean Semiotics of Toxic Masculinity in Indonesian Film - Ramadhani, Angeli; Sopacua, Yustina; Alfredo, Ronald (Universitas Pattimura, 2023)
This article aims to describe the representation of toxic masculinity in the Indonesian film Vengeance Is Mine, All Others Pay Cash through a semiotic analysis of the main character and selected scenes, employing John Fiske’s three-level coding model: the levels of reality, representation, and ideology. The analysis focuses on visual and narrative elements such as costume, behavior, cinematography, lighting, dialogue, and the actions of the protagonist, Ajo Kawir. The findings reveal that toxic masculinity is portrayed through 1980s-style modest clothing that symbolizes a duality of toughness and vulnerability, acts of violence as dominance over other men, and the refusal to fight women as a sign of patriarchal superiority. At the representation level, cinematographic techniques such as medium shots, close-ups, two-shots, and over-the-shoulder shots emphasize the emotional and violent dimensions of the character. Ideologically, the film articulates values of individualism, male dominance, and superiority, shaped by past trauma and patriarchal social structures. This study demonstrates that film serves not only as entertainment but also as a site for the production and reproduction of problematic gender ideologies. Its novelty lies in the application of Fiske’s semiotic approach to deconstruct toxic masculinity in contemporary Indonesian cinema.